(untitled) - Read, Shirley (Amsterdam, 2008)
Creating and organizing successful photography exhibitions requires business finesse and expertise as well as artistic ability. Exhibiting Photography offers step-by-step guidance, paired with anecdotes and case studies of real situations to help photographers at any level improve their business skills, explore new exhibiting techniques and learn to self promote with confidence.
Keywords: Photography,Nhiếp ảnh; Exhibitions,Triển lãm v.v